Qatar's School Transportation System Supporting Safety, Efficiency, and Service Quality - Henry, Keith (RAND Corporation, 2012)
In consideration of the many challenges associated with Qatar's continued growth and demographic changes, the government of Qatar is interested in updating its school transportation system (STS). This volume assesses parents' and school administrators' perspectives on Qatar's STS, identifies a vision and goals for the STS, and discusses strategies to achieve the vision and better align Qatar's STS with international norms.